Effect of Stray and High Voltage Exposure on Livestock: An Overview - Dr Sanjay T Parmar,; Dr N B Patel,; Dr Durgga Rani V.,; Dr T K S Rao, (Indian Journal of Animal Production and Management, 2024)
Electricity is essential to dairy farming and electrically powered machines are used for milking, automatic feed dispensers and heated water bowls. Leakage of current from these equipments, high voltage lines or faulty connections between the electrical circuit and the earth can lead to an undesirable electrical phenomenon called stray voltage. Stray voltage is a small voltage ( 6 mA (up to 10): Feed intake is reduced, resulting in lower meat and milk production. Common symptoms of stray voltage in cows include hesitation to enter the parlor, they may stampede or rush out of the parlor when released, cows dance or step around constantly while in the milking parlor, Normal milk letdown is interrupted, Increased milking time, Udder irritation caused by residual milk and increased somatic cell count which increases the incidence of mastitis.